Madeline - Bemelmans, Ludwig, 1898-1962. (New York : Viking, 1967)
Madeline, smallest and naughtiest of the twelve little charges of Miss Clavel, wakes up one night with an attack of appendicitis.
Caldecott Medal/Honor
School Library Journal
Wilson's Children
Booklist, November 2007
Bulletin (Center for Children's books), November 2007
Horn Book, October 2007
Keywords: Ilness -- Fiction; Stories in rhyme; Caldecott Medal; Ilness -- Fiction; Stories in rhyme; France -- Fiction; France -- Fiction